2010
DOI: 10.1016/j.concog.2009.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Contingency learning and unlearning in the blink of an eye: A resource dependent process

Abstract: Recent studies show that when words are correlated with the colours they are printed in (e.g., MOVE is presented 75% of the time in blue), colour identification is faster when the word is presented in its expected colour (MOVE in blue) than in an unexpected colour (MOVE in green).The present series of experiments explored the possible mechanisms involved in this colourword contingency learning effect. Experiment 1 demonstrated that the effect was already present after 18 learning trials. During subsequent unle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
120
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(142 citation statements)
references
References 33 publications
19
120
3
Order By: Relevance
“…We then compared high, medium, and low contingency trials. Unsurprisingly, high contingency trials were responded to significantly suggest that contingencies are learned quickly and remain relatively stable throughout the task (Schmidt et al, 2007(Schmidt et al, , 2010Schmidt & De Houwer, 2012b, 2012d. conditions were small (<0.5%) and in the opposite direction to those predicted by the misprediction cost and bidirectional cost accounts.…”
Section: (Figure 3)mentioning
confidence: 99%
See 1 more Smart Citation
“…We then compared high, medium, and low contingency trials. Unsurprisingly, high contingency trials were responded to significantly suggest that contingencies are learned quickly and remain relatively stable throughout the task (Schmidt et al, 2007(Schmidt et al, , 2010Schmidt & De Houwer, 2012b, 2012d. conditions were small (<0.5%) and in the opposite direction to those predicted by the misprediction cost and bidirectional cost accounts.…”
Section: (Figure 3)mentioning
confidence: 99%
“…Unbeknownst to participants, each word is presented most often in one colour (e.g., "find" most often in red, "list" most often in green, etc.). Participants implicitly learn these contingencies very rapidly (Schmidt, De Houwer, & Besner, 2010), as indicated by faster responses to high contingency trials (where the word accurately predicts the response) relative to low contingency trials (where the word does not correctly predict the response).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, learning is dependent on having available memory resources (Schmidt & Besner, 2008), but does not seem to require contingency awareness (Schmidt, Crump, Cheesman, & Besner, 2007). Most critically, in addition to being a very simple paradigm to program and use, the resulting contingency effect is extremely reliable (i.e., very small sample sizes are required) and is acquired very quickly (e.g., significant in the first block of 18 trials in Schmidt, De Houwer, & Besner, 2010), making it a highly advantageous approach to study learning.…”
Section: Testing the Generality Of Contingency Learning In A Performamentioning
confidence: 99%
“…In particular, they suggested that participants calculate the expected response based on the identity of the word and use this response prediction to decrease the response threshold of the predicted response. An even simpler explanation is that "contingency learning" is simply a by-product of memory storage and retrieval processes (see Schmidt, De Houwer, & Besner, 2010). Specifically, on each trial participants encode information about what stimuli (word and colour) were presented along with what response was made into an episodic memory.…”
Section: Adaptation In the Item-specific Proportion Congruent Paradigmmentioning
confidence: 99%
“…Although not key for the simulations reported in the current series, this reconsolidation process allows the model to rapidly adapt to changes in contingency (e.g., see Schmidt et al, 2010).…”
Section: Contingency and Conflict Adaptation 32mentioning
confidence: 99%